Health Service Delivery in Fragile, Conflict, and Violence Situations - Hasumi, Takahiro (World Bank, Washington, DC, 2018)
This report is part of the Fragile, Conflict, and Violence (FCV) health knowledge notes series that highlights operational tips to resolve health issues in FCV situations. In FCV situations, successful service delivery depends on extensive situational analysis (for example, political economy, forms of violence, rent-seeking behavior/motivations), close monitoring and flexibility and rapid response mechanism against shocks or threats. This report answers five questions related to FCV situations and service delivery.